First-Principles Calculations of Thermoelectric Properties of IV–VI Chalcogenides 2D Materials - Morales-Ferreiro, J. O.; Diaz-Droguett, D. E.; Celentano, D.; Luo, T. (Frontiers in Mechanical Engineering, 2017)
A first-principles study using density functional theory and Boltzmann transport theory has been performed to evaluate the thermoelectric properties of a series of single layer 2D materials. The compounds studied are SnSe, SnS, GeS, GeSe, SnSe2, and SnS2, all of which belong to the IV-VI chalcogenides family. The first fourth compounds have orthorhombic crystal structures, and the last two have hexagonal crystal structures. Solving a semi-empirical Boltzmann transport model through the BoltzTraP software, we compute the electrical properties, including Seebeck coefficient, electrical conductivity, power factor and the electronic thermal conductivity, at three levels of carrier concentrations (1018, 1019 and 1020 cm-3). The spin orbit coupling (SOC) effect on these properties is evaluated and is found not to influence the results significantly. First-principles lattice dynamics combined with the iterative solution of phonon Boltzmann transport equations are used to compute the lattice thermal conductivity of these materials. It is found that these materials have narrow band gaps in the range of 0.75-1.58 eV. Based on the highest values of figure-of-merit ZT of all the materials studied, we notice that the n-type materials generally have better thermoelectric properties than the p-type ones. The best thermoelectric materials at low temperature (300 K) are SnSe, SnS, and GeS, and at high temperature (800 K) are SnSe at 10^18, 10^19 cm-3 respectively, and SnSe2, at 10^20 cm-3 levels of carrier concentration.